Brief communication: lessons learned and experiences gained from building up a global survey on societal resilience to changing droughts - de Macedo, Marina Batalini; Benso, Marcos Roberto; Sass, Karina Simone; Mendiondo, Eduardo Mario; da Silva, Greicelene Jesus; da Silva, Pedro Gustavo Câmara; Shrimpton, Elisabeth; Sarmah, Tanaya; Huo, Da; Jacobson, Michael; Konak, Abdullah; Balta-Ozkan, Nazmiye; et al. (Copernicus Publications, 2024)
This paper describes the process of creating a global survey of experts to evaluate drought resilience indicators. The lessons learned include five main points: (1) the heterogeneity in the conceptual background should be minimized before the construction of the survey; (2) large numbers of indicators decrease the engagement of respondents through the survey, and ways to apportion indicators whilst maintaining reliability should be considered; (3) it is necessary to design the survey to balance response rate and accuracy; (4) the survey questions should have clear statements with a logical and flowing structure; and (5) reaching experts with different domain experience and representing different regions is difficult but crucial to minimize biased results.